간호대학 시뮬레이션 교육의 이행(transition)에 대한 개념 분석 - 하이경; 방활란; 이연희; Ha, Yi Kyung; Bang, Hwal Lan; Lee, Yeon Hee (Chunghwanja Kanho Hakhoe chi, 2019)
Purpose : The purpose of this study was to identify the attributes, antecedents, and consequences of the transition of simulation-based learning (SBL) in nursing schools. Methods : The study was conducted in accordance with Walker and Avant's conceptual analysis process. We searched MEDLINE, CINAHL, EMBASE, Google Scholar, and RISS (Korean Education and Research Information Service) databases, resulting in nine studies for an in-depth review. Results : The attributes of transition of SBL include (1) preparing for a professional role, (2) practicing in a real clinical setting, and (3) progressing toward expected competency. Antecedents of the concept include novice status, changing roles, clinical experience in controlled settings, and expected competency in the clinical setting. Conclusion : The transition of SBL includes the important feature of progression toward expected competency. Further research is needed to identify graduate nurses' experiences during this transition to establish a strategy for improving it and developing a measurement tool that reflects attributes of the concept.